Предмет: Алгебра,
автор: vovadan17
Упростите выражение
(frac{x}{y} - frac{y}{x}) * frac{y}{x+1} - 1
( frac{ a^{2}}{a+b} - frac{a^{3} }{ a^{2}+2ab+ b^{2} }) *( frac{1}{x} + frac{1}{ x^{2} } )
Ответы
Автор ответа:
0
(x-z)(x+z)×6x÷3x²×z(z+x)=2(x-z)÷xz= ((1-x^2)*y)x^2*y*(x+1) = (1-x^2)(x^2*(x+1)) = (1-x)x^2
Я не знаю правильно или нет
Я не знаю правильно или нет
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Математика,
автор: voloshinawww909
Предмет: Биология,
автор: Starmy1
Предмет: Математика,
автор: Julja99
Предмет: Математика,
автор: jolidonmd